2022
DOI: 10.1063/5.0103597
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic imaging of superconducting qubit devices with scanning SQUID-on-tip

Abstract: We use a scanning superconducting quantum interference device (SQUID) to image the magnetic flux produced by a superconducting device designed for quantum computing. The nanometer-scale SQUID-on-tip probe reveals the flow of superconducting current through the circuit as well as the locations of trapped magnetic flux. In particular, maps of current flowing out of a flux-control line in the vicinity of a qubit show how these elements are coupled, providing insight on how to optimize qubit control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…(3) JJs and SQUIDs for on-tip sensors. FIB-based milling [57], irradiation [63] and deposition [93] seem convenient to create superconducting sensors on tips and cantilevers, in particular JJs and SQUIDs, with the potential to investigate relevant physical properties of materials and devices at the nanoscale [58]. These specialized sensors could represent a niche for FIB-based processing given that the use of standard lithography might be possible here, but difficult for up-scaling [110,111].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) JJs and SQUIDs for on-tip sensors. FIB-based milling [57], irradiation [63] and deposition [93] seem convenient to create superconducting sensors on tips and cantilevers, in particular JJs and SQUIDs, with the potential to investigate relevant physical properties of materials and devices at the nanoscale [58]. These specialized sensors could represent a niche for FIB-based processing given that the use of standard lithography might be possible here, but difficult for up-scaling [110,111].…”
Section: Discussionmentioning
confidence: 99%
“…The resulting SQUID-on-tip (SOT) sensor has been used to image small magnetic signals with high lateral resolution [57]. Moreover, such SOT sensors have been applied to image the magnetic flux arising from a superconducting qubit [58]. • Superconducting microwave resonators in the proximity of qubits are of great interest to control them, which can be fabricated by Ga + -FIB [59,60] as well as by Ne + -FIB with a better resolution [61].…”
Section: Focused Ion Beam (Fib) Patterning Of Superconductorsmentioning
confidence: 99%
“…Their CD imaging results intuitively distinguished CD pattern differences between a normal and faulty status, however, were unable to offer CD directions [13]. E. Marchiori et al showed the CD in the superconducting qubit circuit using a superconducting quantum interference device (SQUID) to give a resolution of 3 mA and a probe-to-sample separation of 600 nm [8].…”
Section: Introductionmentioning
confidence: 99%
“…Existing MCIs primarily use Fourier transform back-evolution for the vertical component of the magnetic field above the DUT to reconstruct its two-dimensional CD magnitude distribution [4,5]. The superiorities of in situ, visibility, and non-invasive conditions promoted MCI applications in the fields of integrated circuit fault diagnosis, superconductor magnet analysis, and lithium-ion battery health prognosis [1,[6][7][8]. Benaiah D. Schrag et al used magnetic tunnel junction sensors to image the CD magnitude in a self-made application-specific integrated circuit.…”
Section: Introductionmentioning
confidence: 99%